2009
DOI: 10.1111/j.1540-8159.2009.02480.x
|View full text |Cite
|
Sign up to set email alerts
|

Alert Tones Are Frequently Inaudible among Patients with Implantable Cardioverter‐Defibrillators

Abstract: Background: Current management guidelines for patients with Medtronic Sprint Fidelis ICD leads (Medtronic Inc., Minneapolis, MN, USA) include prominent use of Patient Alert TM , a feature in which the ICD generator emits audible beeps at two programmable frequencies. Because hearing loss is highly prevalent beyond the sixth decade of life, the utility of this feature is unclear. Therefore, we conducted a survey of patients' ability to hear the Medtronic Patient Alert TM . Methods: During visits to an outpatie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…However, management must be tailored to patient risk. The Lead Integrity Alert algorithm is limited to patients with Medtronic pulse generators, does not provide advanced warning in approximately 25% of patients, and is limited in part by the inability of older patients to hear alert tones (26). Clinical predictors of lead failure include higher ejection fraction (27), age Ͻ50 years, and, possibly, sports/physical activity (10).…”
Section: Multivariate Predictors Of Mortalitymentioning
confidence: 99%
“…However, management must be tailored to patient risk. The Lead Integrity Alert algorithm is limited to patients with Medtronic pulse generators, does not provide advanced warning in approximately 25% of patients, and is limited in part by the inability of older patients to hear alert tones (26). Clinical predictors of lead failure include higher ejection fraction (27), age Ͻ50 years, and, possibly, sports/physical activity (10).…”
Section: Multivariate Predictors Of Mortalitymentioning
confidence: 99%
“…Indeed, it has been reported that patients frequently do not hear or respond to the audible alert. 23,24 In contrast, in the remote arm, the clinician was automatically notified of the alert condition, and no direct patient interaction was required; this reduced potential patient compliance issues. Data were promptly reviewed, and triage of patients could be performed remotely.…”
Section: Landolina Et Almentioning
confidence: 99%
“…We had insufficient data to determine the reasons for delay in each case; however, we are aware of individual cases in which either patients or physicians misinterpreted audible alerts or patients did not hear the alert tone. 26 Use of remote monitoring with wireless-telemetry ICDs permits automatic transmission of LIA notifications and might reduce delays if physicians respond promptly. In the present study, too few patients had automated LIA notifications transmitted by remote monitoring to determine whether automatic alerts reduce shocks caused by lead fractures.…”
Section: Clinical Approach After Lia Warningmentioning
confidence: 99%